Chromato-mass-spectometric determination of components of thick extracts from immature walnut fruit - Ye. V. Zalygina; O. A. Podpletnya; K. V. Sokolova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Topicality. To date, one third of medicines are derived from medicinal plant raw materials and every year the medicinal plants continue to cause increasing interest among doctors. Phytopreparations are attracted by the fact that their use is accompanied by a minimum of side effects, they do not interact with other medicines, they help restore and normalize vital processes, provide the body with the necessary minerals and vitamins, maintain a certain level of metabolism and are successfully used in many chronic diseases.